Two new composite plate elements with bond–slip effect for nonlinear finite element analyses of FRP-strengthened concrete slabs. (February 2015) - Teng, Xiaodan; Zhang, Y.X.; Lin, Xiaoshan
Abstract: Two 8-node 48-DOF rectangular composite layered plate elements, CPEB-1 and CPEB-2, which account for the bond–slip effect between FRP sheets and concrete, are developed for nonlinear finite element analyses of FRP-strengthened concrete slabs in this paper. A layered approach is used to form an integrated plate element for modelling of concrete, FRP, adhesive layer and steel reinforcement and also for modelling of debonding. In element CPEB-1, a zero thickness interfacial element is used to connect concrete and FRP layer and to model the debonding between concrete and FRP layer. In element CPEB-2, the bond–slip is assumed to occur within a smeared layer with real thickness, which connects the concrete tensile zone with the adhesive layer. Shear deformation effects are included in these models and the shear locking problem is avoided by employing the Timoshenko's composite beam functions to describe the deflection and rotation of the layered plate elements. Both geometric and material nonlinearity are included. The accuracy and efficiency of the proposed elements are validated by comparing the computed results with experimental results obtained from literatures. The two elements and their computation accuracy and computation effectiveness are also compared.